2018
DOI: 10.4103/1319-2442.229266
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum soluble urokinase plasminogen activator receptor as a marker for steroid-responsiveness in children with primary nephrotic syndrome

Abstract: Nephrotic syndrome (NS) is the most common primary glomerular disease among children. It runs a relapsing course involving prolonged periods of treatment with corticosteroids and other immunosuppressive medications. Soluble urokinase plasminogen activator receptor (suPAR) has been regarded as an inflammatory as well as a permeability factor. The aim of our study was to evaluate serum suPAR levels in children with NS and its relation to steroid responsiveness. Our study was carried out on 75 children who were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This finding is in contrast with Peng et al (28) results, reporting that su-PAR level was different between SRNS and SSNS groups. Furthermore, Peng and Mousa et al also found that supAR was significantly higher in SRNS patients compared to the SSNS, SDNS, and normal population (23). stated that suPAR levels are specifically associated with primary FSGS, and chronic overexpression of suPAR leads to an FSGS-like nephropathy in mice, and treatment with mycophenolate mofetil was associated with a lower serum su-PAR level (26,60).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This finding is in contrast with Peng et al (28) results, reporting that su-PAR level was different between SRNS and SSNS groups. Furthermore, Peng and Mousa et al also found that supAR was significantly higher in SRNS patients compared to the SSNS, SDNS, and normal population (23). stated that suPAR levels are specifically associated with primary FSGS, and chronic overexpression of suPAR leads to an FSGS-like nephropathy in mice, and treatment with mycophenolate mofetil was associated with a lower serum su-PAR level (26,60).…”
Section: Discussionmentioning
confidence: 96%
“…However, just recently, the usefulness of the soluble urokinase plasminogen activator receptor as a biomarker in clinically estimating and differentiating SRNS was corroborated (14,15,(20)(21)(22)(23)(24)(25)(26)(27). Some studies also reported that using suPAR level, it is possible to distinguish whether FSGS patients are responsive or resistant to therapy (23,28). Wei et al (26) stated that the serum concentrations of this receptor are significantly elevated in patients with FSGS compared to healthy subjects and in pre-transplant patients who later develop the recurrent form of this syndrome after transplantation (26,29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Soluble urokinasetype plasminogen activator recep tor (suPAR) suPAR was once postulated to be the circulating permea bility factor in FSGS or SRNS 65) , but it was soon refuted by several studies 66,67) . Regarding predictive markers of steroid responsiveness in children with NS, two studies were found 68,69) . While individual studies reported the significance of this molecule in distinguishing SRNS from SSNS, meta analysis of these two studies was not significant (Fig.…”
Section: Peripheral Blood Markersmentioning
confidence: 99%
“…Serum soluble urokinase-type plasminogen activator receptor (SuPAR) is a glycosylphosphatidylinositol (GPI)-anchored protein on the cell membrane secreted during infections and inflammation [15]. SuPAR is expressed in various cell types such as machrophages, monocytes, endothelial cells, neutrophil, certain cancer cells and kidney podocytes [16].…”
Section: Introductionmentioning
confidence: 99%